Shaking the Heavens and Splitting the Earth - Cliff, Roger (RAND Corporation, 2011)
This monograph analyzes published Chinese and Western sources about current and future capabilities and employment concepts of the People's Liberation Army Air Force (PLAAF). It describes how those capabilities and concepts might be realized in a conflict over Taiwan, assesses the implications of China implementing them, and provides recommendations about actions that should be taken in response.